1996
DOI: 10.1021/ja953403l
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Palladium(II)-Catalyzed Synthesis of Five- or Seven-Membered Ring Lactones and Five-, Six- or Seven-Membered Ring Lactams by Cyclocarbonylation Methodology

Abstract: 2-Allylphenols react with carbon monoxide and hydrogen in the presence of catalytic quantities of a cationic palladium(II) complex [(PCy 3 ) 2 Pd(H)(H 2 O)] + BF 4 -or palladium acetate and 1,4-bis(diphenylphosphino)butane, affording five-or seven-membered ring lactones (bicyclic, tricyclic, and pentacyclic) as the principal products, often in excellent yields. Use of 2-aminostyrenes as reactants and catalytic quantities of palladium acetate and tricyclohexylphosphine, affords five-membered ring lactams in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 164 publications
(53 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…9,10 A few years ago we reported that the combination of palladium acetate (Pd(OAc) 2 ) and 1,4-bis-(diphenylphosphino) butane (dppb) formed an efficient homogeneous catalytic system for the selective cyclocarbonylation of allyl phenols and other bis-allyl phenols. 11,12 The reaction afforded new important five-, six-and sevenmembered ring lactones (Scheme 1) and it has been noted that the solvent can play an important role in terms of yield and regioselectivity: in toluene, for example, the seven-membered ring lactone was the major product; in dichloromethane, the six-and five-membered lactones were favoured.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 A few years ago we reported that the combination of palladium acetate (Pd(OAc) 2 ) and 1,4-bis-(diphenylphosphino) butane (dppb) formed an efficient homogeneous catalytic system for the selective cyclocarbonylation of allyl phenols and other bis-allyl phenols. 11,12 The reaction afforded new important five-, six-and sevenmembered ring lactones (Scheme 1) and it has been noted that the solvent can play an important role in terms of yield and regioselectivity: in toluene, for example, the seven-membered ring lactone was the major product; in dichloromethane, the six-and five-membered lactones were favoured.…”
Section: Introductionmentioning
confidence: 99%
“…Proton attack from X and metal elimination affords cyclic carbonyl compounds D [see refs. 24,28,33,39,72,89].…”
Section: Brief Overview On the Functional Groups Involved And Proposementioning
confidence: 99%
“…According to a recent study cyclocarbonylation of 2-allylphenol derivatives, using Pd(OAc)2 and dppb as catalytic system, gave mixture of five, six and seven membered ring lactones (Scheme 31) [39].…”
Section: Five- Six-and Seven-membered and Bis-lactones Fused To Arommentioning
confidence: 99%
“…1,2 In 1996, one of us described the regioselective cyclocarbonylation of 2-allylphenol derivatives, using palladium acetate [Pd(OAc) 2 ] and 1,4-bis(diphenylphosphino)butane (dppb) as a homogeneous catalytic system, for the synthesis of five-, six-or seven-membered ring lactones, and it was found that the selectivity of the process was dependent on the solvent and CO/H 2 ratio. 3 More recently, the previously mentioned catalytic system has been validated for the synthesis of a large variety of molecules, such as bis-lactones and estrone derivatives. 4,5 To our knowledge, very few examples of heterogeneous catalysis are reported in the literature for this class of reaction.…”
Section: Introductionmentioning
confidence: 99%